Perancangan dan Pelatihan Penggunaan Website Kearsipan Data Sebagai Sarana Digitalisasi dan Peningkatan Akses Informasi PKPRI Surakarta - Milviana, Melya; Mohamad Alif Syekh Mali; Syifa Nur Fadilah; Nuur Laila Khoirun Nisa; Aisyah Jihan Nabilah; Muhammad Ahib Ibrilli (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2025)
The Employee Cooperative of PKPRI Surakarta still relies on a manual archiving system, which is considered ineffective and inefficient, particularly in terms of recording, storing, and retrieving documents. This condition highlights the need for innovation through the implementation of a web-based digital archiving system. This study aims to describe the urgency of implementing a digital archiving system to improve the quality of archive management within the cooperative. Several methods were used in this research, including data collection through interviews, observations, document studies, system requirements analysis, system development methods, and system testing methods. As a follow-up to the system development, the research team also conducted training sessions on the use of the archiving website for the cooperative’s internal staff. The implementation of the web-based digital archiving system is considered capable of providing easier access, enhanced data security, and faster archiving and retrieval processes, thereby improving the overall effectiveness and efficiency of the cooperative’s operations.